Connecting sounds : the social life of music - Crossley, Nick, 1968- (Manchester University Press, 2020)
An original and compelling account of the social nature of music and its interplay with the wider society to which it belongs. Crossley explores the doing and meanings of music, as well as its interface with economic, political and wider social structures.